Creative English Teaching as a Pathway to Student Empowerment and Language Growth in Primary Classrooms - Ratnadimarta, Fitriyana (Journal of Indonesian Society Empowerment, 2025)
This community service initiative explores how creative and innovative teaching methods can empower elementary school students in English language learning. Through a practice-based action approach, the service provider implemented storytelling, role-playing, interactive games, and multimedia tools over six weeks to promote language acquisition and student development in terms of confidence, participation, and self-expression. Data were collected through classroom observations, student feedback, reflective journals, and teacher-student interactions. The findings show that creative methods significantly increased student engagement and motivation while enhancing their ability to use English in meaningful, real-life contexts. These methods fostered a sense of agency among students, enabling them to take more active roles in their learning process. Moreover, the reflective cycles within the action approach allowed ongoing refinement of strategies to meet individual student needs. In conclusion, integrating creative teaching approaches contributes to elementary school learners' linguistic and personal empowerment, supporting their broader educational and social development. Pengabdian ini mengeksplorasi bagaimana metode pengajaran kreatif dan inovatif dapat menjadi sarana untuk memberdayakan siswa sekolah dasar dalam pembelajaran bahasa Inggris. Melalui pendekatan pengabdian berbasis praktik, penulis menerapkan metode seperti bercerita, bermain peran, permainan interaktif, dan alat multimedia selama enam minggu untuk mempromosikan tidak hanya perolehan bahasa tetapi juga perkembangan siswa dalam hal kepercayaan diri, partisipasi, dan ekspresi diri. Data dikumpulkan melalui observasi kelas, umpan balik siswa, jurnal reflektif, dan interaksi guru-siswa. Hasil pengabdian menunjukkan bahwa metode kreatif secara signifikan meningkatkan keterlibatan dan motivasi siswa serta meningkatkan kemampuan mereka menggunakan bahasa Inggris dalam konteks nyata yang bermakna. Metode ini juga membangun rasa agen di antara siswa, memungkinkan mereka untuk mengambil peran yang lebih aktif dalam proses pembelajaran mereka. Selain itu, siklus reflektif dalam pengabdian memungkinkan penyempurnaan strategi yang berkelanjutan untuk memenuhi kebutuhan siswa secara individual. Kesimpulannya, mengintegrasikan pendekatan pengajaran kreatif berkontribusi pada pemberdayaan linguistik dan personal siswa sekolah dasar, serta mendukung perkembangan pendidikan dan sosial mereka secara lebih luas.